Diagnosis sitologi tumor venereal menular anjing pada seekor anjing domestik jantan yang belum dikebiri. - Abellisa, Abellisa; Etriwati, Etriwati; Erwin, Erwin; Ajis, Fikri Alsidik (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Canine transmissible venereal tumors (CTVT) are one of the few naturally occurring transmissible cancers in mammals and pose a significant challenge to canine populations worldwide. Transmitted through coitus, this contagious round-cell neoplasm affects the external genitalia of dogs, highlighting the importance of early diagnosis to prevent tumor progression and limit transmission. Cytological evaluation provides a rapid, reliable, and minimally invasive diagnostic approach that enables the definitive identification of CTVT based on its cellular morphology. A two-year-old intact male domestic dog presented with chronic preputial discharge and genital discomfort. Physical examination revealed a reddish, cauliflower-like mass at the base of the penis. Cytological analysis of the preputial exudate revealed numerous round lymphoblast-like cells with a high nuclear-to-cytoplasmic ratio, prominent nucleoli, and frequent mitotic figures, consistent with CTVT. No therapeutic interventions were performed. This case reinforces the value of cytological examination as a diagnostic tool for genital tumors in dogs, facilitating prompt clinical decision-making and supporting disease management in endemic regions.